The fear of COVID-19 scale: Its structure and measurement invariance across 48 countries - Sawicki, Artur J; Żemojtel-Piotrowska, Magdalena; Balcerowska, Julia M; Sawicka, Monika J; Piotrowski, Jarosław; Sedikides, Constantine; Jonason, Peter K; Maltby, John; Adamovic, Mladen; Agada, Attisso Mathieu Désiré; Ahmed, Oli; Al-Shawaf, Laith; et al. (Psychological assessment, 2022)
Coronavirus disease (COVID-19) has been a source of fear around the world. We asked whether the measurement of this fear is trustworthy and comparable across countries. In particular, we explored the measurement invariance and cross-cultural replicability of the widely used Fear of COVID-19 scale (FCV-19S), testing community samples from 48 countries (N = 14,558). The findings indicate that the FCV-19S has a somewhat problematic structure, yet the one-factor solution is replicable across cultural contexts and could be used in studies that compare people who vary on gender and educational level. The validity of the scale is supported by a consistent pattern of positive correlations with perceived stress and general anxiety. However, given the unclear structure of the FCV-19S, we recommend using latent factor scores, instead of raw scores, especially in cross-cultural comparisons. (PsycInfo Database Record (c) 2022 APA, all rights reserved).
Keywords: reprodukovatelnost výsledků; Fear; COVID-19; strach; Humans; SARS-CoV-2; lidé; psychometrie; Reproducibility of Results; Psychometrics